2022
DOI: 10.1182/blood.2022016765
|View full text |Cite
|
Sign up to set email alerts
|

KIR3DL2 contributes to the typing of acute adult T-cell leukemia and is a potential therapeutic target

Abstract: Adult T-cell leukemia (ATL) is a lymphoid neoplasm caused by HTLV-1, that encodes the transcriptional activator Tax, which participates in the immortalization of infected T cells. ATL is classified into four subtypes (ie, smoldering, chronic, acute, lymphoma). We determined whether natural killer receptors (NKR) were expressed in ATL. NKR expression (KIR2DL1/2DS1, KIR2DL2/2DL3/2DS2, KIR3DL2, NKG2A, NKG2C, NKp46) was assessed in a discovery cohort of 21 ATL, and KIR3DL2 was then assessed in 71 ATL patients. KIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Previous studies have explored the role of these molecules in cancers. Cheminant et al found that KIR3DL2 is a underlying target of acute adult T‐cell leukemia 45 . Meanwhile, FCRL1 was also reported as a possible prognostic marker for diffuse large B‐cell lymphoma 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have explored the role of these molecules in cancers. Cheminant et al found that KIR3DL2 is a underlying target of acute adult T‐cell leukemia 45 . Meanwhile, FCRL1 was also reported as a possible prognostic marker for diffuse large B‐cell lymphoma 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the role of these molecules in cancers. Cheminant et al found that KIR3DL2 is a underlying target of acute adult T-cell leukemia 45.…”
mentioning
confidence: 99%
“…To target lymphoma cells, the anti-KIR3DL2 mAb Lacutamab (IPH4102, IgG1), a humanized monoclonal anti-KIR3DL2 antibody was developed [77]. Preclinical data revealed promising results for Lacutamab, efficiently enabling autologous NK-cells to eliminate KIR3DL2 + primary ATLL cells in ex vivo assays [78]. In addition to ATLL, a Phase I trial for CTCL evaluated the safety and activity of Lacutamab in a cohort of 44 r/r CTCL patients (NCT02593046) [79].…”
Section: Targeting Kir3dl2 By Lacutamabmentioning
confidence: 99%
“… 4 We have also recently shown that KIR3DL2 is the only KIR recurrently expressed in ATL, mostly in acute subtypes. 5 …”
mentioning
confidence: 99%
“… 11 Moreover, we recently demonstrated that HTLV-1 infection triggered KIR3DL2 expression by normal CD4 + cells after 7 days of cell culture, suggesting that HTLV-1 influences KIR3DL2 expression either through infection-dependent chronic antigenic stimulation, viral integration, or the transcriptional activity of viral proteins. 5 Thus, in PTCL, it is conceivable that KIR3DL2, expressed either because of lineage properties or downstream of chronic antigenic stimulation, promotes PTCL cell survival through its inhibitory functions on the TCR pathway leading to reduced AICD.…”
mentioning
confidence: 99%